SOCIO-ECONOMIC AND ENVIRONMENTAL DETERMINANTS OF SUISTAINABLE DEVELOPMENT OF RURAL COMMUNES IN MAŁOPOLSKA PROVINCE - Paluch, Łukasz; Sroka, Wojciech (Acta Scientiarum Polonorum. Oeconomia, 2013)
Disproportions of economic, social and environmental in the development of rural areas occur at every level of an administrative division of a country. These disproportions are applicable to the actions which are and should be taken not only to better the economic situation of rural areas, but to increase the standard of living for the villagers as well. The aim of this article is both to identify and to evaluate the influence of factors which characterize the level of socio-economic development of environmental sustainability of rural communes in Małopolska Province. Analyses are based on multiple regression model which represents the approach used by Classical Statistics Analysis (enables the observation of the correlation between multi dimensional structures). Research embraces 125 rural communes, with the exception of urban and urban-rural communes, in Małopolska Province. The conducted researches demonstrate that factors of economic nature, particularly the size of own incomes of a commune and means of EU project financing, exert the most powerful influence on the level of environmental sustainability of the researched rural communes.